Linking workplace digitalization to work engagement: evidence from China public sector organizations - Xiaohui Zhan; Shenghua Xie (Frontiers in Psychology)
PurposeThe construction of “Digital Government” has greatly facilitated the workplace digitalization in the public sectors of China. Workplace digitalization has become a pervasive phenomenon in modern organizations, including the public sector. Existing research on the impact of workplace digitalization on individual behavior has yielded conflicting results, making the impact of workplace digitalization on employee work engagement remains a subject of debate and investigation. Based on the transactional theory of stress, this article aims to examine how workplace digitalization influences government employees’ work engagement through different appraisals (i.e., challenge and threat) and the moderating role of a personal trait (i.e., digital literacy).MethodsStructured questionnaires and a three-wave research design were used to collect data. A total of 290 employees from public organizations in Guangdong Province, in China, participated in the study. SPSS and MPLUS were used to analyze the data using the latest bootstrapping and process macro techniques.ResultsThe results show that workplace digitalization can produce both beneficial and detrimental impacts on work engagement of government employees via challenge and threat appraisals, respectively. The digital literacy of government employees was confirmed to moderate the impacts of perceived workplace digitalization on stress appraisals (i.e., challenge and threat).ConclusionOur study proposes a theoretical framework that explain the mixed impacts of workplace digitalization on government employees’ work engagement via challenge and threat appraisals. It also offers practical suggestions to public sector and managers on how to balance the challenge and threat aspects of digitalization in the workplace.